Description of a new species of giant guitarfish, Glaucostegus younholeei sp. nov. (Rhinopristiformes: Glaucostegidae) from the northern Bay of Bengal, Bangladesh - Habib, Kazi Ahsan; Islam, Md Jayedul (Zootaxa, 2021)
A new species of giant guitarfish, Glaucostegus younholeei sp. nov., is described from 13 specimens, 730–933 mm total length, collected from fish landing center of Bangladesh Fisheries Development Corporation in Cox’s Bazar district of Bangladesh. The new species is distinguished from congeners in having the following combination of characters: Body brownish or greyish in color with a narrowly wedge-shaped disc, and long narrow bluntly pointed snout (angle 31–40°), and broad oblique nostrils with the narrow anterior opening. Nostrils about half of the mouth width, subequal (0.98–1.33) to internasal width; ~55–57 nasal lamellae; anterior nasal flaps slightly penetrating into internasal space, their interspace 2.20– 2.61 in length of the posterior nasal aperture. Orbit very small in adults, diameter 8.19–11.62 in preorbital length, 2.25–2.69 in interorbital space. Rostral ridges almost joined along their entire length; margin of cranium sharply demarcated before eyes. Spiracular folds very short and widely separated. Skin rough, densely covered with small denticles, more coarsely granular on the dorsal surface than ventrally, enlarged between orbits and in a distinct band between nape and first dorsal fin. Tail relatively longer, length 1.15–1.48 in disc length; dorsal fins narrowly spaced, interspace 1.32–2.11 in base length of the first dorsal fin. Clasper length in adult male 4.37–5.70 in total length. Phylogenetic analysis of DNA barcode sequences also shows the clear divergence of Glaucostegus younholeei from other congeneric species obtained from GenBank. A key is provided to the 8 known members including new species of the genus Glaucostegus.